PSIKOEDUKASI “STARTING WITH YOURSELF” SEBAGAI UPAYA PENINGKATAN KEPEMIMPINAN DIRI DAN KINERJA OPTIMAL - A'yun, Qurrota; Raja Oloan Tumanggor; P. Tommy Y. S. Suyasa (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
This Community Service Program aimed to enhance the understanding and skills of employees at PT MTI in applying self-leadership as an effort to achieve optimal performance within a dynamic work environment. The program was implemented through a psychoeducational webinar entitled “Starting with Yourself,” which was attended by 110 employees from various divisions and job levels, demonstrating a high level of participation. The psychoeducational content covered fundamental leadership concepts, behavior-focused strategies, natural reward strategies, and constructive thought strategies. Evaluation was conducted using pre-test and post-test assessments to measure improvements in participants’ understanding. The results indicated a significant increase in employees’ knowledge after joining the webinar, as reflected in their enhanced ability to comprehend, integrate, and apply self-leadership concepts compared to their initial understanding prior to the program. Active engagement in ice-breaking activities, discussions, and question-and-answer sessions further contributed to the effectiveness of the learning process. These findings suggest that psychoeducation is an effective method for strengthening employees’ self-regulation capacities and readiness to meet the demands of work in the telecommunication industry. This program is expected to serve as a foundation for the development of subsequent leadership-based training initiatives aimed at continuously improving the quality of human resources.